P075 Initial results of an international effort in screening new agents against Candida auris. (20th September 2022) - Poester, Vanice; Munhoz, Lívia; Melo, Aryse; Benelli, Jéssica; Al-Hatmi, Abdullah; Larwood, David; Martinez, Marife; Stevens, David; Xavier, Melissa
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Candida auris is an emergent fungal pathogen. A global concern regarding this yeast is its resistance to many currently available antifungal drugs, virulence factors, capacity to spread in hospital environments, and its misidentification, resulting in high rates of morbidity, and mortality. Objective: In response to this challenge, new effective options of antifungals against C. auris are urgent. Therefore, our consortium evaluated the in vitro activity of two agents with novel mechanisms of action, and negligible toxicity in studies to date: diphenyl diselenide (PhSe)2 and nikkomycin Z (NikZ), alone and in association with conventional antifungals (azoles, echinocandins, polyenes) against C. auris . Methods: A total of 11 isolates of C. auris were included in this in vitro study, 10 from South Asian clade I and 1 from South Africa clade III. In vitro tests (dilution and interaction assays) were performed according to the CLSI M27-Ed4 protocol. Interactions between (PhSe)2 or nikkomycin Z, and amphotericin B (AmB), fluconazole (FCZ), micafungin (MYC), or caspofungin (CSP) were evaluated by checkerboard assays, resulting in Fractional Inhibitory Concentration Indexes (FICi). Tests were read after incubation for 48 h at 35° C. The minimal inhibitory concentration (MIC) was defined as the lowest concentration able to inhibit 100% (PhSe)2, AmB and NikZ, or 50% (FCZ, MYC, and CSP) of the fungal growth. Interaction between the drugs was classified as strong synergism when FICi <0.5, weak synergism when 0.5 <FICi <1, additive when 1 <FICi <2, indifferent when FICi = 2, or antagonistic when FICi >2. Results: (PhSe)2 and NikZ alone were unable to inhibit C. auris even by the higher concentrations tested (32  μ g/ml and 64–128  μ g/ml, respectively). An additive effect of (PhSe)2 was detected with MYC against 30% of the isolates, however, its combination with AmB was antagonistic against all of the isolates, as well as against one isolate with FCZ. All of the other interactions with (PhSe)2 were indifferent. In contrast, NikZ showed strong or weak synergism in association with CSP, AmB, FLU and MYC against 100%, 90%, 30% and 14% of the C. auris isolates tested, respectively. An additive interaction of NikZ was also detected with MYC against 86% of the isolates. No antagonistic effect was detected in the combination of NikZ with the antifungals tested. Conclusion: Although (PhSe)2 seems to not have potential as a future anti- C. auris drug, NikZ showed a productive avenue for further studies, mainly in combined therapy against this pathogen.